Strategic Planning of Intelligence and Security Agency of the Indonesian National Police in Maintaining Public Security and Order: The Case of the 2020 Omnibus Law Demonstrations - Adi, Bimo Prasetyo; Runturambi, Arthur Josias Simon; Delima, Sylvia Prisca (CV. Proaksara Global Transeduka, 2026)
The October 2020 protests against the Job Creation Law, marked by mass mobilization and significant unrest, tested Indonesia's public security framework. This study analyzes the strategic planning and early detection mechanisms employed by the Intelligence and Security Agency of the Indonesian National Police (Baintelkam Polri) in mitigating threats to public security during the 2020 Job Creation Law protests. Using a qualitative case study approach, data were collected through in-depth interviews with ten key Baintelkam Polri informants and analysis of relevant documents. The findings reveal that strategic planning was conducted through a structured intelligence cycle involving multidimensional risk analysis, cross-functional coordination, and continuous adaptation. Early detection was executed via integrated field and digital monitoring, comprehensive vulnerability indicators, and a rapid field reporting system. Intelligence products centrally informed operational decisions, while rapid estimation mechanisms enabled adaptive responses to emerging threats. The research concludes that intelligence-led early detection and strategic planning are crucial for maintaining security stability during large-scale demonstrations while upholding legal and democratic norms. Theoretically, it reinforces early detection theory and Conflict Early Warning Systems (CEWS) in domestic security, offering empirical insights into central intelligence’s role in managing mass actions in Indonesia.